Sifat-Sifat Fisika Batuan Pulau Biak dan Pulau Supiori, Irian Jaya - Simamora, W.H (Pusat Survei Geologi, 2006)
The stratigraphical units of Biak, Irian Jaya Quadrangle, scale 1:250.000 consist of the Tertiary volkanic and sedimentary rocks, the pre-Tertiary metamorphics and recent alluvial. The studied area is in Biak and Supiori Islands, Irian Jaya bounded by longitudes 135°45' - 136°23'E and latitudes 0°36' - 1°36'S. Thirty six rock samples from investigated area have been collected and analyzed in a laboratory. The physical characteristics of samples analyzed include density (?), porosity (ô), magnetic susceptibility (?), and velocity of seismic wave ( Vp and Vs ). The result shows that the value of densities are within the range of 1.86 - 2.60 gr/cc, permeability -6 2.31 - 35.27%, magnetic susceptibilities are whitin 2,2 - 32,23 x 10 cgs emu The value of wave velocities (Vp) are around 2.2 - 5.4 km/sec, and Vs are within 1.1 - 3.1 km/sec. The result of rock samples analysed in area indicates that density distribution of less than 2.0 gr/cc and permeability distribution of > 20% may have high degree of water saturation. Keywords : Rock physical, density, porosity, magnetic susceptibility, velocity of seismic wave